1988
DOI: 10.1136/bmj.296.6636.1562
|View full text |Cite
|
Sign up to set email alerts
|

Impaired renal functional reserve and albuminuria in essential hypertension

Abstract: The stimulatory effects of an infusion of amino acids on glomerular filtration rate has previously been used to measure renal functional reserve and detect glomerular hyperfiltration. Thirty four patients with mild to moderate essential hypertension and seemingly normal renal function and 22 healthy controls were given infusions of amino acids to investigate whether renal functional reserve is reduced in essential hypertension and to detect patients at risk of renal damage. Although basal creatinine clearance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1
3

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 16 publications
1
24
1
3
Order By: Relevance
“…133 Recent cross-sectional reports in non-diabetic populations 51 do, however, suggest a more complicated picture. High-normal albuminuria rather than microalbuminuria may, in fact, represent the initial and easily missed stage associated with hyperfiltration, followed by normalisation of glomerular filtration rate in the presence of microalbuminuria.…”
Section: Renal Dysfunctionmentioning
confidence: 89%
“…133 Recent cross-sectional reports in non-diabetic populations 51 do, however, suggest a more complicated picture. High-normal albuminuria rather than microalbuminuria may, in fact, represent the initial and easily missed stage associated with hyperfiltration, followed by normalisation of glomerular filtration rate in the presence of microalbuminuria.…”
Section: Renal Dysfunctionmentioning
confidence: 89%
“…13 In a recent study, a similar observation was made in normotensive non-insulin-dependent diabetic patients. 14 The possibility that microalbuminuria is associated with an impaired renal functional reserve assessed by the GFR response to an acute infusion of amino acids was explored by Losito et al 15 It was observed that one third of 34 patients (most of whom were microalbuminuric) with mild to moderate essential hypertension displayed an abolished response of creatinine clearance (a rather unreliable marker of GFR) to this maneuver. In our studies, protein intake (as assessed by urinary excretion of urea) was higher in microalbuminuric when compared with normoalbuminuric patients.…”
Section: Discussionmentioning
confidence: 99%
“…In 1 study, 11 of 34 hypertensive individuals were nonresponders; in 8 of the 11, the UAE was above the normal range. 29 Other studies 30,31 did not found alterations in the increase of GFR induced by an oral protein load in All of the values in the table correspond to samples obtained at baseline of the day of L-arginine infusion. The values from urine samples correspond to the baseline collection periods, before L-arginine administration.…”
Section: Discussionmentioning
confidence: 99%